The Effect of Organizational Culture on Employee Performance, with Collectivism as a Mediating Variable and Power Distance as a Moderating Variable at the Darul Fikri Foundation in Makassar - Rusdi Hidayat Jufri; Deni Gustiawan; Winaya Purwanti; Asep Saifudin (Eduvest - Journal of Universal Studies, 2026)
Employee performance is a critical factor in determining organizational success, particularly in educational institutions where teacher and staff performance directly impacts the quality of educational services and public trust. However, performance variations among employees at the Darul Fikri Foundation in Makassar indicate that performance is not yet fully optimal and consistent, suggesting the need to examine broader organizational factors beyond individual capabilities. This research aims to analyze the influence of organizational culture on employee performance with collectivism as a mediating variable at the Darul Fikri Foundation in Makassar. The research approach uses a quantitative method with regression-based data analysis techniques and mediation tests to examine the direct and indirect relationships between variables. The results show that organizational culture has a positive and significant effect on employee performance, and has a strong influence on collectivism. Collectivism is also proven to have a positive influence on employee performance and acts as a mediating variable in the relationship between organizational culture and performance. These findings indicate that organizational cultural values that emphasize togetherness, cooperation, and collective responsibility can increase employee collective orientation, which ultimately has an impact on improved performance. Thus, strengthening a consistent organizational culture oriented towards collective values is an important factor in creating optimal and sustainable employee performance, especially in the context of educational institutions.